2007
DOI: 10.1111/j.1365-2966.2007.12011.x
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton observations of the eclipsing polar V2301 Oph

Abstract: We present XMM-Newton observations of the eclipsing polar V2301 Oph which cover nearly 2.5 binary orbital cycles and 2 eclipses. This polar is believed to have the lowest magnetic field strength (7 MG) of any known polar. We find evidence for structure in the X-ray eclipse profile which shows a `standstill' feature lasting 26+/-4 sec. This allows us to place an upper limit on the mass of the white dwarf of ~1.2 Msun. We find no evidence for QPOs in the frequency range 0.02-10 Hz. This coupled with the absence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The white dwarf mass is not strictly determined, but an upper limit of M < 1.2 M is found from the eclipse modelling and it is suggested that an acceptable range is M = 1.0-1.1 M . (Ramsay & Cropper 2007). Using a distance of 150 pc, an unabsorbed bolometric X-ray luminosity of L x = 2 × 10 32 erg s −1 is derived from the spectral analysis of the bright phase during the XMM observations by Ramsay & Cropper (2007).…”
Section: V2301 Ophmentioning
confidence: 99%
“…The white dwarf mass is not strictly determined, but an upper limit of M < 1.2 M is found from the eclipse modelling and it is suggested that an acceptable range is M = 1.0-1.1 M . (Ramsay & Cropper 2007). Using a distance of 150 pc, an unabsorbed bolometric X-ray luminosity of L x = 2 × 10 32 erg s −1 is derived from the spectral analysis of the bright phase during the XMM observations by Ramsay & Cropper (2007).…”
Section: V2301 Ophmentioning
confidence: 99%
“…In the few systems lacking distinct soft X-ray emission, such as 2XMMp J131223.4+173659 (Vogel et al 2008) and V2301 Oph (Ramsay & Cropper 2007), the flux maximum of the reprocessed component appears to be shifted towards the EUV and UV regime. The same could apply to objects that show a detectable, but very weak soft component, such as EV UMa (Ramsay & Cropper 2003).…”
Section: Flux Ratios From Multi-temperature Spectral Modelingmentioning
confidence: 99%
“…In most AM Her stars, the soft component originates from the heated atmosphere of the white dwarf around the accretion spot. Thus, 2XMM1312 joins the group of now 9 out of ∼80 polars without a soft component (Ramsay & Cropper 2007). A likely explanation for the non-detection of the soft component is its low temperature which shifts the emission towards lower energies not covered by the X-ray cameras of the XMM-Newton.…”
Section: = 28 × 10mentioning
confidence: 99%